Model Persamaan Struktural Untuk Intention to Stay: Studi Pada Karyawan Bank BJB Cabang Sumber Cirebon - Gendis Shuqie Aurell; Ahyar Yuniawan (Faculty of Economics and Business Diponegoro University, 2025)
Human resources play an essential role in organizational sustainability, as employees are key to achieving company goals. One of the challenges in human resource management is maintaining employees’ intention to stay in the organization. This study aims to analyze the effect of Work-Life Balance and Perceived Organizational Support on Intention to Stay, with Employee Engagement as a mediating variable. The population in this study consisted of permanent employees of Bank BJB Sumber Cirebon Branch. A sample of 100 respondents was selected using purposive sampling techniques. The data was collected through questionnaires and analyzed using Structural Equation Modeling with the SmartPLS 4.1 software. The analysis used includes outer model testing, inner model testing, and testing of direct and indirect effects. The results showed that work-life balance has a positive but not significant effect on intention to stay, while perceived organizational support has a positive and significant effect. Furthermore, Employee Engagement significantly mediates the relationship between both Work-Life Balance and Perceived Organizational Support toward Intention to Stay.